Piezoresistive effect of plain-weave CFRP fabric subjected to cyclic loading. (4th May 2017) - Nishio, Yusuke; Todoroki, Akira; Mizutani, Yoshihiro; Suzuki, Yoshiro
Abstract : The present study deals with electrical resistance changes in woven-fabric CFRP during loading. Four kinds of plain weave woven-fabric CFRP laminated specimens are prepared and subjected to cyclic tensile loading that does not cause any damages, and the electrical resistance changes of the specimens are measured experimentally by the four-probe method. As a result, the present study shows that the electrical resistance of a specimen comprised of six ±45° plies decreases remarkably with increasing number of loading cycles. The decrease is caused by shear plastic deformation of ±45° plies. The thickness shrinkage caused by shear plastic deformation increases the number of fiber contacts, and this decreases the interlaminar contact resistance between the plies. For a single ±45° ply, the same electrical resistance decrease caused by the shear plastic deformation is observed, and the magnitude of the decrease is smaller than that of the six-ply laminate tested. This is because the effect of interlaminar contact resistance decrease does not exist for a single ±45° ply. For the six 0°/90° plies, the present study shows that electrical resistance in the through-thickness direction is decreased by out-of-plane plastic deformation of carbon fiber and misalignment of the plies.